FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PERUMAHAN TIPE CLUSTER DI KOTA SIDOARJO - Andriandita Wijayanto; Sosio Prastiwi Armadani (Yos Soedarso Economic Journal (YEJ), 2020)
House is representing requirement of human being base besides food and clothing. In its growth in the reality house also represent interesting invesment alternative on the chance of capital gain in the future. The analyzer for this research is using doubled linear regression. This Research responder is dweller of housing of Sidoarjo City. Based on result of analysis indicate that price, facility, location, environmental, substitution price and earnings have an effect on to decision of purchasing of house. From the examination of coefficient of determination has known that 68,6 % from variation of that happened in variable decision of purchasing by together in influencing by variable perception of price, facility, location, environmental, substitution price and earnings. While the rest equal to 31,4 % influenced by other factors. Based on the result of this research we got that facility factor very having an effect on in purchasing of house. Seen from level of coefficient influencing decision of purchasing of facility equal to 0,486; earnings equal to 0,443; location equal to 0,340; environment equal to 0,296; substitution price equal to 0,283; and price equal to 0,268Keyword : House ; Facility; Location; Price; Investment.